Νήσος Ορθοδόξων: Ο Αρχιμανδρίτης Κυπριανός και η θρησκευτική Ανθρωπογεωγραφία της Μεσαιωνικής και πρώϊμης Νεότερης Κύπρου - ΚΥΡΙΑΚΟΥ Χρυσοβαλάντης (Byzantina Symmeikta, 2022)
Archimandrite Kyprianos (d. 1802–1805) is the leading historian of Cyprus during its Ottoman period (1571–1878). Initially a translator of Steffano Lusignano’s "Chorograffia" (Bologna, 1573), Kyprianos decided to write his "Chronological History of the Island of Cyprus" (Venice, 1788), in order to stress the Byzantine Orthodox identity of his homeland and to promote the moral dimension of Cypriot history for his Muslim-ruled Orthodox compatriots. The aim of this paper is to explore how Kyprianos portrayed the religious anthropogeography of medieval (Byzantine, Frankish and Venetian) and early modern (Ottoman) Cyprus, by comparing his presentation to that of Lusignano, Logizos Skevophylax (ca. 1600) and other sources. Based on Karl Mannheim’s theory on the sociology of knowledge and recent research on religious geography, the paper traces tendencies of identity inclusion and exclusion in Lusignano, Skevophylax and Kyprianos, approaching the archimandrite’s treatise as an “anti-colonial” narrative, the echo of which is still traceable in Cypriot historiography.